Iowa Gambling Task performance in individuals with schizophrenia: the role of general versus specific cognitive abilities - Orm, Stian; Øie, Merete Glenne; Haugen, Ingvild (Frontiers in Psychiatry, 2024)
ObjectiveWe aimed to explore how specific cognitive processes, such as attention and executive functions, account for variance in decision-making measured by Iowa Gambling Task (IGT) performance among individuals with schizophrenia spectrum disorders.MethodsAdults (N = 65, Mage = 25.4) with schizophrenia spectrum disorders participating in a clinical trial (registered at clinicaltrials.gov NCT03048695) completed the IGT, neuropsychological tests of attention, response inhibition, mental flexibility, working memory, and planning, as well as subtests from the Wechsler tests of intelligence to estimate IQ. Associations between performance on specific tasks, a composite score of executive function and attention, and IGT performance measured in two ways, one using the total net score, decks (C+D) – (A+B) and the other as preference for decks with more frequent gains than losses, decks (B+D) – (A+C), were analyzed with correlational and hierarchical regression analysis controlling for estimated IQ and psychotic symptoms, measured by the Positive and Negative Syndrome Scale.ResultsIn the regression analyses, the strongest predictor of IGT performance measured as the total net score was estimated IQ (b = 1.43, p <.001). Neither specific cognitive tasks nor the composite score of executive functioning significantly contributed to explaining variance in IGT total net score beyond IQ and symptoms of psychosis. However, IQ and symptoms of psychosis did not predict tendency towards selecting decks with different gain-to-loss frequency, whereas poorer composite executive functioning predicted a pattern of selecting decks A and C with more frequent losses, (b = 8.30, p <.05).DiscussionThe results suggest that both IQ and executive functions contribute to IGT performance, but in distinct ways. Whereas lower IQ may contribute to overall more disadvantageous decision-making, poorer executive functioning may contribute to a more risk-aversive decision-making style. A clinical implication may be that individuals with schizophrenia and lower IQ or poorer executive functioning will have a higher need for support and interventions targeting decision-making.